2009
DOI: 10.1007/s00198-009-1136-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of calcitriol therapy in the management of bone loss and fractures: a qualitative review

Abstract: Summary Osteoporosis, a skeletal disorder characterized by a reduction in bone strength, increases fracture risk. Primary osteoporosis is usually a result of reduced bone mineral density as a consequence of natural aging. Secondary osteoporosis is usually a result of a disease, such as cystic fibrosis, or medical treatment, such as corticosteroids or cancer treatment. Introduction Currently, ten million Americans are osteoporotic and an additional 34 million have the precursor condition, osteopenia. Osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 118 publications
1
26
0
Order By: Relevance
“…As reported in a systematic review, calcitriol has been proven to be effective in decreasing or even reversing the rate of bone loss in a variety of vulnerable populations in trials lasting up to 8 years, especially when administered together with bone antiresorptive agents [63]. As expected, the prolonged use of calcitriol yields the common side effects of hypercalciuria and mild hypercalcemia, usually in the mild range, without any report of deaths or lifethreatening hypercalcemic episodes.…”
Section: Endocrinementioning
confidence: 66%
See 3 more Smart Citations
“…As reported in a systematic review, calcitriol has been proven to be effective in decreasing or even reversing the rate of bone loss in a variety of vulnerable populations in trials lasting up to 8 years, especially when administered together with bone antiresorptive agents [63]. As expected, the prolonged use of calcitriol yields the common side effects of hypercalciuria and mild hypercalcemia, usually in the mild range, without any report of deaths or lifethreatening hypercalcemic episodes.…”
Section: Endocrinementioning
confidence: 66%
“…While 25-monohydroxylated vitamin D (calcidiol) may be used to optimize vitamin D status especially when the activity of hepatic hydroxylases is diminished [62], 1a-hydroxylated vitamin D analogs can be employed when renal hydroxylation is impaired, such as in the case of kidney failure or hypoparathyroidism, in order to favor calcium absorption and/or overcome the age-related decreased VDR expression [60,61,63].…”
Section: Rationale For the Clinical Use Of Vitamin D Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…α-Klotho also regulates the expression of vitamin D receptor [42]. It is clear that the lack of 1,25-dihydroxyvitamin D 3 can lead to osteoporosis [43]. Studies have shown that the introduction of variant KL-VS of the human KLOTHO gene in mice enhances cognitive function and increases serum α-klotho levels [44].…”
Section: Renal Endocrine and The "Kidney Stores Essence" Theorymentioning
confidence: 99%